2017
DOI: 10.1093/femsle/fnx130
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of two new cell-bound bioactive compounds produced by wild Lactococcus lactis strain

Abstract: Novel compounds and innovative methods are required considering that antibiotic resistance has reached a crisis point. In the study, two cell-bound antimicrobial compounds produced by Lactococcus lactis ID1.5 were isolated and partially characterized. Following purification by cationic exchange and a solid-phase C18 column, antimicrobial activity was recovered after three runs of RPC using 60% (v/v) and 100% (v/v) of 2-propanol for elution, suggesting that more than one antimicrobial compound were produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The hydrophobic interaction chromatography performed on the re‐run gave good antilisterial activity in 10% isopropanol eluent in which the bacteriocin was found to be pure with a single peak having retention time of 15.86 min (Figure c). This strategy has been applied by many researchers to purify bacteriocins (Khochamit, Siripornadulsil, Sukon, & Siripornadulsil, ; Sahoo, Jena, Patel, & Seshadri, ; Saraiva et al, ; Sawa et al, ), however, other techniques such as fast protein liquid chromatography (FPLC) and filter assisted size exclusion protein fractionation were employed to speed up the purification of bacteriocins (Choi, Cheigh, Kim, & Pyun, ; Chumchalova, Stiles, Josephsen, & Plockova, ). The inhibitory activity, specific activity, and yield of bacteriocin KJBC11 obtained are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobic interaction chromatography performed on the re‐run gave good antilisterial activity in 10% isopropanol eluent in which the bacteriocin was found to be pure with a single peak having retention time of 15.86 min (Figure c). This strategy has been applied by many researchers to purify bacteriocins (Khochamit, Siripornadulsil, Sukon, & Siripornadulsil, ; Sahoo, Jena, Patel, & Seshadri, ; Saraiva et al, ; Sawa et al, ), however, other techniques such as fast protein liquid chromatography (FPLC) and filter assisted size exclusion protein fractionation were employed to speed up the purification of bacteriocins (Choi, Cheigh, Kim, & Pyun, ; Chumchalova, Stiles, Josephsen, & Plockova, ). The inhibitory activity, specific activity, and yield of bacteriocin KJBC11 obtained are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…lactis A164 (isolated from Kimchi) after ammonium sulphate precipitation and tenfold purification was achieved. Saraiva et al 2014 found 20% recovery and 10 fold increases in specific activity after ammonium sulphate precipitate. For the removal of salt the precipitate was dialyzed against distilled water and concentrated to original volume.…”
Section: Purification Of the Bacteriocinsmentioning
confidence: 88%